Delusional belief.[article]. - Coltheart, Max
Delusional beliefs are seen in association with a number of neuropatholgical conditions, including schizophrenia, demntia, and traumatic brain injury. A key distinction exists between polythematic delusion and monothematic delusion. (from the authors)